1999
DOI: 10.1128/aem.65.7.3084-3094.1999
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Bradyrhizobia from Aeschynomene spp. Are Specific to Stem-Nodulated Species and Form a Separate 16S Ribosomal DNA Restriction Fragment Length Polymorphism Group

Abstract: We obtained nine bacterial isolates from root or collar nodules of the non-stem-nodulated Aeschynomene species A. elaphroxylon, A. uniflora, or A. schimperi and 69 root or stem nodule isolates from the stem-nodulated Aeschynomene species A. afraspera, A. ciliata, A. indica,A. nilotica, A. sensitiva, and A. tambacoundensis from various places in Senegal. These isolates, together with 45 previous isolates from variousAeschynomene species, were studied for host-specific nodulation within the genus Aeschynomene, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 51 publications
4
54
0
1
Order By: Relevance
“…Sequence similarity of NodA from those photosynthetic strains with other NodA Bradyrhizobium species was low (63%). These data are in full agreement with previous phylogenetic studies, which showed that photosynthetic Aeschynomene strains form a homogeneous and distinct cluster [3], for which a new species should be proposed. Conversely, NodA sequences from the non-photosynthetic Group I and II strains intertwined with the other species of Bradyrhizobium (Fig.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Sequence similarity of NodA from those photosynthetic strains with other NodA Bradyrhizobium species was low (63%). These data are in full agreement with previous phylogenetic studies, which showed that photosynthetic Aeschynomene strains form a homogeneous and distinct cluster [3], for which a new species should be proposed. Conversely, NodA sequences from the non-photosynthetic Group I and II strains intertwined with the other species of Bradyrhizobium (Fig.…”
Section: Resultssupporting
confidence: 92%
“…In spite of testing numerous primers de¢ned from the consensus region of either NodA, NodB or NodC, we did not succeed in isolating the common nod genes from Group III photosynthetic strains. These results indicate a great divergence of the symbiotic genes as compared with the other rhizo- Acacia nilotica II + [3] bia, which could be related to the extreme narrow host-speci¢city of the Group III photosynthetic strains. Sequence analysis revealed that the nodA gene sequences from Groups I and II non-photosynthetic Bradyrhizobiumtested strains are polymorphs with a percentage of similarity ranging from 73.78 to 96.62% at the DNA level.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…They may therefore grow on atmospheric methanol and consequently alter atmospheric chemistry. Bacterial strains belonging to the genus Bradyrhizobium fix nitrogen, and several Bradyrhizobium strains can carry out photosynthesis (Molouba et al, 1999). Their diverse metabolic capacities could be an advantage in the atmospheric environment, where at least some bacteria may be limited with bioavailable organic compounds.…”
Section: Cultivable Bacterial Communitymentioning
confidence: 99%